Sports drink intake pattern affects exogenous carbohydrate oxidation during running - Mears, S. A.; Boxer, B.; Sheldon, D.; Wardley, H.; Tarnowski, C. A.; James, L. J.; Hulston, C. J. (Medicine & Science in Sports & Exercise, 2020)
Purpose : This study aimed to determine whether the pattern of carbohydrate sports drink ingestion during prolonged submaximal running affects exogenous carbohydrate oxidation rates and gastrointestinal (GI) comfort. Methods: Twelve well-trained male runners (27 ± 7 yr; 67.9 ± 6.7 kg; V?O2peak, 68 ± 7 mL·kg-1·min-1) completed two exercise trials of 100 min steady-state running at 70%V?O2peak. In each of the trials, 1 L of a 10% dextrose solution, enriched with [U-13C] glucose, was consumed as either 200 mL every 20 min (CHO-20) or 50 mL every 5 min (CHO-5). Expired breath and venous blood samples were collected at rest and every 20 min during exercise. Subjective scales of GI comfort were recorded at regular intervals. Results: Average exogenous carbohydrate oxidation rates were 23% higher during exercise in CHO-20 (0.38 ± 0.11 vs 0.31 ± 0.11 g·min-1; P = 0.017). Peak exogenous carbohydrate oxidation was also higher in CHO-20 (0.68 ± 0.14 g·min-1 vs 0.61 ± 0.14 g·min-1; P = 0.004). During exercise, total carbohydrate oxidation (CHO-20, 2.15 ± 0.47; CHO-5, 2.23 ± 0.45 g·min-1, P = 0.412) and endogenous carbohydrate oxidation (CHO-20, 1.78 ± 0.45; CHO-5, 1.92 ± 0.40 g·min-1; P = 0.148) were not different between trials. Average serum glucose (P = 0.952) and insulin (P = 0.373) concentrations were not different between trials. There were no differences in reported symptoms of GI comfort and stomach bloatedness (P > 0.05), with only 3% of reported scores classed as severe (=5 out of 10). Conclusion: Ingestion of a larger volume of carbohydrate solution at less frequent intervals during prolonged submaximal running increased exogenous carbohydrate oxidation rates. Neither drinking pattern resulted in increased markers of GI discomfort to a severe level.